Risk financing for rural climate resilience in the Greater Mekong Subregion. (Metro Manila, Philippines Asian Development Bank, 2017)
This report presents the findings of a climate risk financing study conducted by the GMS Core Environment Program in 28 rural communities in Cambodia, the Lao Peoples Democratic Republic, and Viet Nam. It provides an overview of the frequency and severity of climate related disasters for the communities, the impact of these on rural livelihoods, and how local people currently manage climate risks. The report also explores what climate risk financing strategies could be applied in such communities, including the potential costs and benefits.
Keywords: Climatic change -- Developing countries; Climate change mitigation -- Economic aspects; Electronic books